Threatening to buy: Private equity buyouts and antitrust policy - Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2018)
Private equity firms (PE firms) have become common owners of established firms in concentrated markets. We show that the threat of a PE acquisition can trigger incumbent mergers in an otherwise mergerstable industry. This can help antitrust authorities maximize consumer surplus because previously privately unprofitable - but consumer surplus-enhancing - mergers now take place. We thus predict that merger waves among incumbents should follow the development of a local PE industry.
Keywords: G32; G34; L13; L22; L40; 330; Antitrust policy; M&As; Private equity; Temporary ownership